Workflows for Advanced Manufacturing in Design. Issue 2 (3rd July 2022) - Tracy, Kenneth J.; Tan, Ying Yi; Bañón, Carlos; Low, Hong Yee
Abstract : Digital Manufacturing and Design Centre Singapore University of Technology and DesignSingapore Established: 2015 Centre Leadership: Low Hong Yee (Director) David William Rosen (Director of Research) Pablo Valdivia y Alvarado (Deputy Director) Current Center Structure: Academic Faculty: 21 Research Staff: 12 Postdoctoral Researchers: 10 Graduate Students: 12 Visiting Faculty and Students: 1